Methodological approaches in research on urban green spaces in the context of coastal tourism development - Darija Perković; Vuk Tvrtko Opačić (Geoadria, 2020)
Urban green spaces, especially those in the coastal areas, are of great and multiple importance for sustainable urban and tourism development. At the same time, they are endangered by excessive construction caused by the urbanisation process. Increased urbanisation occurs as the consequence of spatial expansion of the built-up land of coastal towns due to strong littoralisation processes, but also as a consequence of an increasing coastal tourism development. Scientific research on the connection between urbanisation and tourism is conducted in various scientific areas and disciplines, representing urban green spaces mainly in a wider context, rarely as immediate objects of research. Understanding and comparison of research results are made difficult due to non-standardised methodology and terminology applied in research. Therefore, the main purpose of this paper is to provide an overview of methods applied in research of urban green spaces and, on its grounds, to select methodological approaches applicable for geographic research on urban green spaces within the context of coastal tourism development. The meaning of “urban green space” and its relationship with tourism were defined. The subject of research, terminology and classification of urban green spaces, spatial and temporal context of research, applied methodology and interpretation of results were analysed. Two most frequent methodological approaches in urban green spaces research in the context of coastal tourism development were identified: a) Comparative spatio-temporal research of transformation of urban green space due to tourism development and b) Research on attitudes and perception of urban green space users within the context of tourism development. The identified approaches are applicable in geographic research of urban green spaces, and they are based on methodological background of the positivist and humanistic-behavioural approach in contemporary geography.